If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3m/5-4=-7
We move all terms to the left:
3m/5-4-(-7)=0
We add all the numbers together, and all the variables
3m/5+3=0
We multiply all the terms by the denominator
3m+3*5=0
We add all the numbers together, and all the variables
3m+15=0
We move all terms containing m to the left, all other terms to the right
3m=-15
m=-15/3
m=-5
| 2=u-84/7 | | 123/5+x=30 | | 4-a*5=64 | | 9+2=12-q= | | -21=-3w-6 | | 23x+1=15x-9 | | 5(b-7)=4b+5 | | q-97/2=1 | | 9p+3=84 | | -8w+5(w-2)=-7 | | 6y-32=40 | | 11z+3=47 | | 5x+85=1495 | | r-60/4=7 | | v-39=7 | | -2(x+5)=6x+4(x-2) | | k+19/6=6 | | 4(1/4+c)=1.25 | | 3.1=1.3-0.5y | | 2q^2–98=0 | | 4x+3×(36-×)=124 | | u/6-16=5 | | 263-w=183 | | 8x^2-8=528 | | 169=76-x | | f-72/7=3 | | 2x+7=5x-4-x | | 4(1/4+c)=1/1/4 | | 260=-w+169 | | 2j-2=22 | | 4(1/4+c)=11/4 | | −4(−1.2x+1)=2.9(x-10)+2.4x |